PENGEMBANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB TERINTEGRASI QR CODE: STUDI KASUS SMP NEGERI 2 PEGANDON - Rochayati Rochayati; Ahmad Ashifuddin Aqham; Bagus Sudirman (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
School libraries are crucial elements in supporting the learning ecosystem. However, SMP Negeri 2 Pegandon still faces significant challenges in manual data management. This research aims to design a web-based library information system that integrates QR Code technology. The development method used a prototyping model, which includes requirements gathering, design planning, and system testing. The results show that this application is able to minimize data duplication, accelerate book search processes, and streamline borrowing and return transactions. The QR Code implementation provides high accuracy in member and collection identification. This system is expected to increase transparency and accountability in school library management.